2013
DOI: 10.1371/journal.pone.0075969
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Soil Properties Influence Survival of Listeria monocytogenes in Soil

Abstract: Listeria monocytogenes is a food-borne pathogen responsible for the potentially fatal disease listeriosis and terrestrial ecosystems have been hypothesized to be its natural reservoir. Therefore, identifying the key edaphic factors that influence its survival in soil is critical. We measured the survival of L. monocytogenes in a set of 100 soil samples belonging to the French Soil Quality Monitoring Network. This soil collection is meant to be representative of the pedology and land use of the whole French ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 49 publications
6
76
0
Order By: Relevance
“…Depending on environmental factors, the chance of L. monocytogenes survival is higher in some soils than in others. These results are consistent with those of a previous study which showed that the survival of L. monocytogenes in soil depended on abiotic properties, in particular, the basic cation saturation ratio, pH, and clay content (42). In our study, pH was the predominant abiotic factor highlighted by the Spearman rank correlation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Depending on environmental factors, the chance of L. monocytogenes survival is higher in some soils than in others. These results are consistent with those of a previous study which showed that the survival of L. monocytogenes in soil depended on abiotic properties, in particular, the basic cation saturation ratio, pH, and clay content (42). In our study, pH was the predominant abiotic factor highlighted by the Spearman rank correlation.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, pH was the predominant abiotic factor highlighted by the Spearman rank correlation. It is known that low pH is detrimental to the survival of L. monocytogenes in soil, but as pH is a structuring parameter for soil microbial communities, it is rather difficult to differentiate the actual direct effect of pH and the indirect role of the composition and structure of the microbial communities on the dynamics of the populations of L. monocytogenes (42). More generally, because the composition and structure of the microbial communities are structured by the complex characteristics of the abiotic environment (43)(44)(45), it is difficult to address the weight of a single parameter on the overall survival of L. monocytogenes in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Important factors that have been speculated to influence the occurrence of L. monocytogenes in soil are soil microbiota, fauna, soil composition, temperature, pH, moisture, and strain motility (2,26,27,28). However, if further insight is to be gained into the unique ecological behavior of L. monocytogenes, it is necessary to map globally occurring genotypes and strains from environmental habitats (29,30).…”
Section: T He Genus Listeria Comprises the Species L Monocytogenes mentioning
confidence: 99%
“…Soil type greatly determines the soil water content. The extended survival of nonpathogenic E. coli and E. coli O157:H7 has been attributed to higher water availability in different soil types (39) and to moisture content (40), while the long-term survival of Listeria monocytogenes in soil has been attributed to soil texture and clay content (41,42). Sandy soils, like the soil in our study, retain less water and have been associated with faster declines in E. coli (43).…”
Section: Discussionmentioning
confidence: 50%